Termination of Shoot Gravitropic Responses by Auxin Feedback on PIN3 Polarity - Rakusová, Hana; Abbas, Mohamad; Han, Huibin; Song, Siyuan; Robert, Hélène S; Friml, Jiří (Current biology, 2016)
Plants adjust their growth according to gravity. Gravitropism involves gravity perception, signal transduction, and asymmetric growth response, with organ bending as a consequence [1]. Asymmetric growth results from the asymmetric distribution of the plant-specific signaling molecule auxin [2] that is generated by lateral transport, mediated in the hypocotyl predominantly by the auxin transporter PIN-FORMED3 (PIN3) [3-5]. Gravity stimulation polarizes PIN3 to the bottom sides of endodermal cells, correlating with increased auxin accumulation in adjacent tissues at the lower side of the stimulated organ, where auxin induces cell elongation and, hence, organ bending. A curvature response allows the hypocotyl to resume straight growth at a defined angle [6], implying that at some point auxin symmetry is restored to prevent overbending. Here, we present initial insights into cellular and molecular mechanisms that lead to the termination of the tropic response. We identified an auxin feedback on PIN3 polarization as underlying mechanism that restores symmetry of the PIN3-dependent auxin flow. Thus, two mechanistically distinct PIN3 polarization events redirect auxin fluxes at different time points of the gravity response: first, gravity-mediated redirection of PIN3-mediated auxin flow toward the lower hypocotyl side, where auxin gradually accumulates and promotes growth, and later PIN3 polarization to the opposite cell side, depleting this auxin maximum to end the bending. Accordingly, genetic or pharmacological interference with the late PIN3 polarization prevents termination of the response and leads to hypocotyl overbending. This observation reveals a role of auxin feedback on PIN polarity in the termination of the tropic response.
Keywords: proteiny huseníčku; Arabidopsis; percepce tíhy; Gravitropism; Plant Shoots; regulátory růstu rostlin; gravitropismus; výhonky rostlin; zpětná vazba fyziologická; Gravity Sensing; Feedback, Physiological; Plant Growth Regulators; kyseliny indoloctové; Arabidopsis Proteins; Indoleacetic Acids